Eleanor Roosevelt’s Peculiar Pacifism: Activism, Pragmatism, and Political Efficacy in Interwar America - Dario Fazzi (European Journal of American Studies)
In the interwar years, American women have played a major role in shaping both the domestic and the international debate on peace, by spreading pacifist tenets and merging them with the promotion of social justice and human rights. Leading figures of the women’s peace campaign such as Emily Balch, Lillian Wald, and Jane Addams have lived their personal struggle for peace as an opportunity to enhance the universal condition of women’s lives and at the same time promote workers’ rights, international disarmament, and the empowerment of the international institutions. Eleanor Roosevelt was not only an integral part of this interwar pacifist chorus, but she also represented one of its most influential voices. Although her biographers have stressed the impact of this period on her political and intellectual formation, a systematic account of her contribution to the shaping of the American interwar pacifism is still missing and this is precisely the broad scope of my article. I will therefore define Eleanor Roosevelt’s peculiar pacifism as one mostly characterized by a prominent inclination toward activism, a pragmatic attitude, and a compelling political efficacy.